Utilisation of health services by the deaf and hard of hearing in kanyama compound - Chisupa,Eric. (Lusaka: University of Zambia , School of Medicine, 2007)
The deaf and hard of hearing is vulnerable group in society. The government of the Republic of Zambia is striving to reach the health related millenium development goals, this also includes provision of health services to all the population including the deaf and hard of hearing. The purpose of the study was to determine the factors influencing underutilization of health services by the and hard of hearing in kanyama compound.
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Deaf --Zambia.; Hearing impaired --health services